Bearing capacity and load transfer of brace topological in offshore wind turbine jacket structure. (1st March 2020) - Zhang, Puyang; Li, Jingyi; Gan, Yi; Zhang, Jinfu; Qi, Xin; Le, Conghuan; Ding, Hongyan
Abstract: With the aim of the developing offshore wind turbines in the deep sea and with the demand for larger capacity turbines, a brace structure was designed to provide guidance for an offshore wind turbine jacket foundation. The influence of the brace structure on the bearing capacity and load transfer mode from the top to bottom of the jacket structure was studied using numerical simulation. The results show that, among various topological structures, the X-type topological mode has great advantages for the bearing capacity. The number of layers can be decreased to reduce the cost of offshore wind power. When the section moment of inertia of the brace is greater, the load on the top of the leg is smaller, and the proportion of the horizontal load on the bottom of the compressive leg is higher. The properties of the brace only affect the bearing capacity of the structure in a small range. Highlights: The load transfer modes and the stress characteristics of the six kinds of jackets under the limit load condition. The X-type topological mode has great advantages for the bearing capacity. The properties of the brace affect the bearing capacity of the structure in a small range.